Tourism in the Post-Pandemic World : Economic Challenges and Opportunities for Asia-Pacific and the Western Hemisphere - Goretti, Manuela (Departmental Papers; Departmental Paper ;, 2021)
This departmental paper analyzes the impact of the COVID-19 pandemic on tourism in the Asia Pacific region, Latin America, and Caribbean countries. Many tourism dependent economies in these regions, including small states in the Pacific and the Caribbean, entered the pandemic with limited fiscal space, inadequate external buffers, and foreign exchange revenues extremely concentrated in tourism. The empirical analysis leverages on an augmented gravity model to draw lessons from past epidemics and finds that the impact of infectious diseases on tourism flows is much greater in developing countries than in advanced economies.